327PNeoantigen profile of hepatocellular carcinoma reveals its correlation with tumour progression and clonal evolution. (24th November 2019) - Liu, X; Li, Z; Cai, Z; Chen, G; Liu, J
Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common malignancies in China with poor prognosis. Recently, personalized neoantigen-based immunotherapy has been reported to induce robust anti-tumor immune responses to facilitate tumor rejection in several solid tumors. However, whether it possess therapeutic potential in HCC still remain unclear. Thus, a systemic understanding of neoantigen burden (TNB) in HCC microenvironment is in need. Methods: HCC and matched peritumor tissue collected from 59 HCC patients were subjected to DNA and RNA sequencing for identifying tumor associated neoantigens. Then the association between neoantigens and clinical features, immune signatures, as well as clonal evolution patterns in HCC were evaluated. Results: In enrolled HCC patients, a median of 106 somatic mutations and 15 neoantigens were identified in each patient. TNB was significantly correlated with tumor somatic mutation burden (R 2 = 0.893, P = 3.0 × 10^ -24 ). Furthermore, the clinicopathological analysis revealed that patients with higher TNB was characterized with older age (p = 0.006), decreased tumor size (p = 0.020) and lower recurrence rate (p = 0.019). Additionally, TNB was also significantly associated with relapse free survival (P = 0.033) and overall survival (P = 0.022) in HCC patients. Surprisingly, HCC tumor with high immune cell infiltration were more likely to have no tumor envelope (P = 0.027) and resulted in shorter overall survival time after surgery (P = 0.025); the patients with lower immune cell signatures related to antigen-processing have relatively higher TNB in HCC. Meanwhile, clonal evolution analysis revealed that the clonal mutations were more likely to be neoantigens ( P = 9.2 × 10^ -5 ) than subclonal mutations, suggesting higher immunogenicity for clonal mutations. And tumors with higher proportion of neoantigens in clonal mutations were more likely to involved in clonal evolution, which may due to the immunoediting of neoantigens (P = 0.002). Conclusions: Our results demonstrated that neoantigens play an important role in tumor clonal evolution and immune response in HCC, which could provide insights for future HCC immunotherapy. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.